Google Classroom Effectiveness Helping Educandy As Learning Media - Endang Astuti; Sri Lestari; Farah Erika (Educational Studies: Conference Series, 2021)
The current pandemic condition, namely the Covid-19 virus, has resulted in various schools having to implement online learning, therefore one of the efforts to help the online learning process to be more fun and not boring is to use learning media in the learning process. This study aims to determine the effectiveness of Google Classroom assisted by Educandy as a learning medium for students' chemistry learning outcomes. The population and sample in this study were all students of class X MIPA as many as 89 students, the sample was determined using a saturated sampling technique. This research method is descriptive quantitative research design with One Group Pretest Posttest Design. Data was collected by means of learning outcomes tests as the main data, student response questionnaires and observation as support data. The data analysis technique used is the n-gain test and the effect size test. The results of the calculations in this study are the average data for the analysis of N-Gain for learning outcomes is 0.625, which means that it is included in the moderate level of effectiveness. And based on the results of the Effect Size test, it obtained a value of 1,077 which means that the learning media used is included in the category of strong effect. The results showed that the use of Google Classroom assisted by Educandy was effective as a learning medium at SMA Negeri 1 Kembang Janggut.